2018
DOI: 10.3758/s13421-018-0792-x
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary and voluntary recall of musical memories: A comparison of temporal accuracy and emotional responses

Abstract: Comparisons between involuntarily and voluntarily retrieved autobiographical memories have revealed similarities in encoding and maintenance, with differences in terms of specificity and emotional responses. Our study extended this research area into the domain of musical memory, which afforded a unique opportunity to compare the same memory as accessed both involuntarily and voluntarily. Specifically, we compared instances of involuntary musical imagery (INMI, or “earworms”)—the spontaneous mental recall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 53 publications
3
31
1
Order By: Relevance
“…One of these shared features is the high faithfulness of musical images. This has been a repeated finding in both indepth qualitative studies (Brown, 2006; and quantitative research (Jakubowski et al, 2018;Jakubowski et al, 2015). Williamson and Jilka (2014) state that musical imagery is frequently "comparable to an actual music listening experience" (p. 667), and INMI experiences can be described as simplified versions of the canonical recording.…”
Section: Veridicality Of Recall In Inmimentioning
confidence: 93%
See 1 more Smart Citation
“…One of these shared features is the high faithfulness of musical images. This has been a repeated finding in both indepth qualitative studies (Brown, 2006; and quantitative research (Jakubowski et al, 2018;Jakubowski et al, 2015). Williamson and Jilka (2014) state that musical imagery is frequently "comparable to an actual music listening experience" (p. 667), and INMI experiences can be described as simplified versions of the canonical recording.…”
Section: Veridicality Of Recall In Inmimentioning
confidence: 93%
“…Scatterplot of the relationship between recorded (canonical) and tapped (imagined) tempo from two studies ofJakubowski et al (2015, N = 130;Jakubowski et al (2018), N = 101 episodes), adapted from the original figure Self-reported frequency of INMI among women (N = 8,144) and men (N = 3,766). Error bars show 99% confidence intervals.…”
mentioning
confidence: 99%
“…Although our music manipulation is not designed to affect participants' mood, we will analyze mood as a function of music condition (Jakubowski et al, 2018;Nineuil et al, 2020;Schulkind et al, 2013). Mood ratings are ordinal Likert-type responses on a 7-point scale, so we will use a cumulative ordinal regression model (as we proposed for the music familiarity manipulation check).…”
Section: Mood Manipulation Checkmentioning
confidence: 99%
“…Elsewhere, it appears that the focus is the inability to manage the imagery, with involuntary musical imagery being described as songs “that get stuck in your head even though you do not want them to stay there” (Beaman and Williams, 2013, p. 402) or “the experience of an inability to dislodge a song and prevent it from repeating itself in one’s head” (Beaman and Williams, 2010, p. 637). Still other definitions state that both the initiation and management are involuntary, such as a “short section of music that comes to the mind spontaneously without effort and then goes on repeating itself without conscious control” (Floridou and Müllensiefen, 2015, p. 472) or “the spontaneous recall and repetition of a piece of music within the mind” (Jakubowski et al, 2018, p. 2). The only scale of involuntary musical imagery experiences defines it as when a “short section of music comes into the mind, spontaneously, without effort, and then repeats without conscious control” (Floridou et al, 2015, p. 28).…”
Section: Major Approaches To Mental Control In Everyday Musical Imagerymentioning
confidence: 99%
“…One study has directly compared involuntary and voluntary musical imagery experiences using a Tempo Judgment paradigm (see Table 1; Jakubowski et al, 2018). They compared people’s perceptions of tempo for involuntarily and voluntarily initiated musical imagery of the same song and found that representation of the tempo for the two episodes was not significantly different.…”
Section: Major Approaches To Mental Control In Everyday Musical Imagerymentioning
confidence: 99%